Institutional allocations in the primary market for corporate bonds - Nikolova, Stanislava; Wang, Liying; Wu, Juan (Julie) (Journal of Financial Economics, 2020)
Using 2002–2014 insurer transactions, we provide the first empirical evidence on underwriters’ allocation practices in the primary market for corporate bonds. Since bonds are often underpriced, allocations generate for investors an estimated $41 billion of first-day profits. These profits increase with proxies for investors’ information production during the bookbuilding process and, more strongly, with investors’ prior trading with underwriters. Information production has a larger impact when asymmetric information is higher, while prior trading has a larger impact when the issuer-underwriter agency problem is more severe. When there is more competition for allocations, prior trading further increases an insurer’s first-day profits.